2014
DOI: 10.1590/s1677-5538.ibju.2014.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide Hydrogel (Bulkamid) in Female Patients of 80 or More Years with Urinary Incontinence

Abstract: Polyacrylamide hydrogel (Bulkamid®) is an effective treatment with low morbility in patients of 80 or more years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…Even the less frequent adverse effects such as chronic urinary retention did not persist on a long-term basis (>1 year). The safety of PAHG has also been studied in women over 80 years and seems to be both effective and result in low morbidity [24]. Moreover, this study also confirmed that PAHG was effective regardless of the presence or absence of urethral hypermobility [24].…”
Section: Findings Of Our Studysupporting
confidence: 68%
See 4 more Smart Citations
“…Even the less frequent adverse effects such as chronic urinary retention did not persist on a long-term basis (>1 year). The safety of PAHG has also been studied in women over 80 years and seems to be both effective and result in low morbidity [24]. Moreover, this study also confirmed that PAHG was effective regardless of the presence or absence of urethral hypermobility [24].…”
Section: Findings Of Our Studysupporting
confidence: 68%
“…The safety of PAHG has also been studied in women over 80 years and seems to be both effective and result in low morbidity [24]. Moreover, this study also confirmed that PAHG was effective regardless of the presence or absence of urethral hypermobility [24]. Another study showed that PAHG used for treatment of stress incontinence showed improvement in sexual function and sexual satisfaction.…”
Section: Findings Of Our Studysupporting
confidence: 56%
See 3 more Smart Citations